Antimicrobial Effects of Ethanol and Acetone Extracts of Plantago major Seed on Streptococcus mutans - S Mozafar; E Majidi; R Bakhtiari; M Norouzi; S Kameli (Journal of Research in Dental and Maxillofacial Sciences, 2023)
Background and Aim: This study aimed to compare the effects of acetone and ethanolic extracts of Plantago major (P. major) on S. mutans. Materials and Methods: In this in vitro study, the antibacterial effects of eight different concentrations of the acetone and ethanolic extracts of P. major seed were examined on S. mutans, and the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the extracts and the inhibition zone diameter were assessed. Results: The acetone extract of P. major seed showed a superior antibacterial effect compared with its ethanolic extract, demonstrating antibacterial effect on S. mutans at 1 mg/mL concentration by the cup plate method and a mean growth inhibition zone diameter of 6±0.2 mm. the MIC and MBC of this extract were 0.5 mg/mL and 1 mg/mL, respectively. The ethanolic extract of P. major seed had an antibacterial effect on S. mutans with a concentration of 0.5 mg/mL by the cup plate method with a mean inhibition zone diameter of 8.3±0.1 mm. The MIC and MBC of this extract were 2 mg/mL and 8 mg/mL, respectively. An increase in the diameter of inhibition zone was seen at higher concentrations of both extracts. The mean diameter of growth inhibition zone of chlorhexidine (CHX) was 24 mm. Conclusion: The present results demonstrated the antibacterial activity of ethanolic and acetone extracts of P. major seed on S. mutans. The acetone extract was more effective than ethanol extract on S. mutans.